Risk Factor for Surgical Site Infection Post Sectio Caesarea - Dedeh Supriyatin; Margareta Melani; Siti Jubaedah; Ari Indra Susanti; Hadi Susiarno (Green Publisher Indonesia, 2025)
Surgical site infections are infections that occur within 30 days of a surgical procedure, including infections in the post-sectio caesarea area that are common and can cause significant morbidity. This study aims to comprehensively identify and analyze the risk factors associated with post-sectio caesarea infection. The method used was a literature review with a PEO framework (Population: post-sectio caesarean section; Exposure: associated risk factors; Result: incidence of infection). Article searches were carried out systematically in official databases such as Google Scholar, Pubmed, Science Direct, and Scopus with the keywords